THE PROCESS OF TRIMMING AND RAISING THE SOIL BY THE WORKING BODIES OF THE SOIL TREATMENT AND SEPARATION INSTALLATION - Syromyatnikov , Yu. N.; Khramov , N. S. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The subject of the research is the process of functioning of disk working bodies and a ploughshare of the soil-cultivating loosening-separating installation, which carries out lifting and separation of the soil. When moving the ploughshare at shallow depths (0.03 ... 0.12 m), the movement of the soil along it is complicated by the formation of a soil roll, which is formed in front of the ploughshare. The soil is loosened and scattered to the sides, not providing the necessary support required to move it to the loosening-separating device. Passive rotating disks are installed on both sides of the ploughshare so that the soil does not clump and scatter to the sides. The object of the study are the disk elements of the lifting and trimming device, which can significantly increase the efficiency of the technological process of soil movement on the ploughshare while reducing the specific energy consumption of the process. The initial information to substantiate the study was obtained by analyzing the literature. It is determined that increasing the radius of parallel freely rotating flat disks from 0.175 to 0.270 m leads to an increase in the thickness of the soil layer on the ploughshare by no more than 17%. With increasing kinematic parameter of rotation of the disks from 0 to 0.6 soil compaction on the ploughshare decreases by 2.73 times, from 0.6 to 1.0 - by 1.25 times and from 1.0 to 1.2 - by 1, 04 times. It is established that increasing the angle of the ploughshare initially leads to a decrease in the soil level on it and reaches a minimum at an angle close to 25 °. With a further increase in the angle, the soil level on the ploughshare increases. It has been experimentally proved that the greatest influence on the limiting distance between the disks at which the lifting of the soil layer by the ploughshare is carried out without jamming is the soil moisture. The relevance lies in the fact that the simultaneous use of passive disk working bodies together with a ploughshare allows to improve the methods of pre-sowing tillage to improve its agronomic qualities.